Оцінка економічної ефективності здійснення екологічно безпечної переробки на прикладі пестициду диметоат - Петрук, Р.В.; Ранський, А.П.; Шиян, А.А. (Екологічна безпека та природокористування, 2012)
The paper investigates the economic component for reagent processing substandard phosphorus containing pesticides on example pesticide dimethoat. Budgeted costs for all types of recycling pesticide and calculated the possible gains from the sale of secondary products. The coefficient of efficiency of processing reagent to obtain as a secondary product additive for lubricants ZnDTP is 9, 48.